Responding to incidents of sexual victimization in correctional institutions: correctional officer perspectives - Cook, Carrie L. (International journal of offender therapy and comparative criminology, 2017)
This study examined beliefs among correctional officers about responding to inmate-on-inmate sexual assault in jails. It is unique in its focus as no other published study has examined this topic using these variables in this setting. The authors utilize survey methodology to measure correctional officer perceptions about responding to sexual assaults among inmates. Results indicate that support for responding to instances of sexual assault among inmates differs somewhat by type of response and size of jail facility examined. Multivariate results suggest that while perceptions of inmate credibility are usually relevant, demographic factors matter more for those who work in larger jails, while beliefs about rape myths are somewhat more relevant in smaller jails. Implications for correctional policy and training and avenues for continued research are discussed